2009
DOI: 10.1021/jp904691g
|View full text |Cite
|
Sign up to set email alerts
|

NMR Investigation of the Dynamics of Confined Water in Nafion-Based Electrolyte Membranes at Subfreezing Temperatures

Abstract: The dynamical characteristics and the thermal analysis of water absorbed in filler-free Nafion and in silica or zirconia phosphate Nafion composites, between 20 and -50 degrees C, were investigated by NMR and DSC techniques. Self-diffusion coefficients and longitudinal NMR relaxation times (T(1)) put in evidence a fraction of water freezing at subzero temperatures. The complementary water fraction remains in the liquid state at least down to -50 degrees C. The freezing point (T(f)) depends on the initial water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 28 publications
5
59
0
1
Order By: Relevance
“…water in swollen Nafion, which range from a few to hundreds of milliseconds. [26,27] This result confirms that the modulation in the x value is not influenced by the intrinsic nuclear-spin relaxation, but by the dynamics of water. From t = 280 ps, the D w value for water molecules near sulfonic acid was computed to be 5.3 10 À10 m 2 s À1 (see equation (5) in the Supporting Information), which is comparable to D w % 6 10 À10 m 2 s À1 found by PFG NMR spectroscopy for swollen Nafion with approximately 20 water molecules per sulfonic acid group.…”
Section: Methodssupporting
confidence: 74%
“…water in swollen Nafion, which range from a few to hundreds of milliseconds. [26,27] This result confirms that the modulation in the x value is not influenced by the intrinsic nuclear-spin relaxation, but by the dynamics of water. From t = 280 ps, the D w value for water molecules near sulfonic acid was computed to be 5.3 10 À10 m 2 s À1 (see equation (5) in the Supporting Information), which is comparable to D w % 6 10 À10 m 2 s À1 found by PFG NMR spectroscopy for swollen Nafion with approximately 20 water molecules per sulfonic acid group.…”
Section: Methodssupporting
confidence: 74%
“…This value compares to a water self‐diffusion coefficient of ∼2 × 10 −10 m 2 s −1 at 273 K. Although this work demonstrates that absorbed water in PFSAs was moving more slowly in the membranes below 0 °C compared to membranes at higher temperatures, there was enough mobility to promote proton transport. Other studies of water mobility at low temperatures showed step changes in the water self‐diffusion coefficient at low temperatures that were attributed to freezing events 47, 48. These membranes were probably more hydrated than the samples studied by Ma et al, which lead to some portion of the water in the membrane freezing.…”
Section: Water Motion and Proton Conductivitymentioning
confidence: 77%
“…16,27 In the model fits to the experimental data of Nafion/DTA þ and Nafion/TMPA þ systems, the contributions of R and SD are not presented separately but are represented by a single curve (R 1 ) RþSD = (R 1 ) R þ (R 1 ) SD , with a prefactor (R 1 ) 0 RþSD and a single correlation time τ c . In Figure 9a,b are presented the best fits obtained with eq 3 to the R 1 experimental results obtained for the Nafion/DTA þ and Nafion/TMPA þ systems.…”
Section: Articlementioning
confidence: 99%